Inhibition of Nitric Oxide (NO) Production in Lipopolysaccharide (LPS)-Activated Murine Macrophage RAW 264.7 Cells by the Norsesterterpene Peroxide, Epimuqubilin A - Leng Chee Chang; John M. Pezzuto; Bahman Rostama; Eun-Jung Park; Sarot Cheenpracha (Marine Drugs, 2010)
Seven norsesterterpene peroxides: epimuqubilin A (1), muqubilone B (2), unnamed cyclic peroxide ester (3), epimuqubilin B (4), sigmosceptrellin A methyl ester (5), sigmosceptrellin A (6), and sigmosceptrellin B methyl ester (7), isolated from the marine sponge Latrunculia sp., were examined with regard to their effects on nitric oxide (NO) production in lipopolysaccharide (LPS)-activated murine macrophage RAW 264.7 cells. The results indicated epimuqubilin A (1) possessed potent NO inhibitory activity against lipopolysaccharide (LPS)-induced nitric oxide release with an IC50 value of 7.4 µM, a level three times greater than the positive control, L-NG-monomethyl arginine citrate, followed by 6 (sigmosceptrellin A, IC50 = 9.9 µM), whereas other compounds exhibited only modest activity (Table 1). These compounds did not show appreciable cytotoxicity at their IC50 values for NO–inhibitory activity. The structure–activity upon NO inhibition could be summarized as follows: (1) a monocyclic carbon skeleton framework was essential for activity,(2) free acids gave higher activity, (3) the orientation of H3-22 with an equatorial position increased activity, and (4) a bicyclic structure reduced activity. This is the first report of a norsesterterpene peroxide with NO–inhibitory activity. In addition, compounds 1–7 were also evaluated for their inhibitory activities in the yeast glycogen synthase kinase-3βassay. In summary, several norsesterterpene peroxides showed novel biological activities of inhibition in NO production, suggesting that these might provide leads for anti-inflammatory or cancer chemopreventive agents.